Examining the complex relationship between Urbanization and ecological environment in ecologically fragile areas: a case study in Southwest China - Liu, Lei; Guo, Yimeng; Li, Yuchao; Zhang, Lanyue (Frontiers in Public Health, 2024)
The sustainable development of ecologically fragile areas and the implementation of regional coordinated development strategy cannot be separated from the coordinated development and common progress of urbanization and ecological environment, and this is particular the case in Southwest China. This study examines the interplay between urbanization and the ecological environment across 26 cities in Southwest China from 2009 to 2019, utilizing 30 statistical indicators to analyze their coupling coordination relationship and its spatiotemporal evolution. Entropy TOPSIS method, coupling coordination degree model and obstacle factors model were used to calculate the subsystem score, coupling coordination degree and its obstacle factors. Our findings reveal an upward trajectory in urbanization scores across the 26 cities, juxtaposed with a fluctuating downward trend in ecological environment scores. The coupling coordination degree of urbanization and ecological environment of most cities maintained a rapid upward trend, and showed spatial distribution characteristics of "strong core, weak middle and edge". Moreover, our analysis identifies public transport facilities, aggregate purchasing power and cultural supply service services as primary obstacle factors impeding the development of coupling coordination degrees. These research results offer valuable insights for informing future endeavors in achieving high-quality development and fostering ecological civilization.